2011
DOI: 10.1074/jbc.m110.211110
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Hypoxia Inducible Factor Hydroxylation Sites to Hypoxia and Hydroxylase Inhibitors

Abstract: Hypoxia inducible factor (HIF) is regulated by dual pathways involving oxygen-dependent prolyl and asparaginyl hydroxylation of its α-subunits. Prolyl hydroxylation at two sites within a central degradation domain promotes association of HIF-α with the von Hippel-Lindau ubiquitin E3 ligase and destruction by the ubiquitin-proteasome pathways. Asparaginyl hydroxylation blocks the recruitment of p300/CBP co-activators to a C-terminal activation domain in HIF-α. These hydroxylations are catalyzed by members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
203
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(224 citation statements)
references
References 50 publications
21
203
0
Order By: Relevance
“…The estimated K m values for oxygen for the PHDs and FIH in vitro are quite different: 250 and 90 mM, respectively (Koivunen et al, 2003). Consistent with this work, a recent study showed in in vivo experiments, using the endogenous human HIF-1a protein, that both prolyl hydroxylation was more sensitive to inhibition to hypoxia (Hx) than asparaginyl hydroxylation (Tian et al, 2011). Thus, the PHD activity should be more sensitive to a moderate decrease in oxygen compared with that of FIH.…”
Section: Introductionsupporting
confidence: 53%
“…The estimated K m values for oxygen for the PHDs and FIH in vitro are quite different: 250 and 90 mM, respectively (Koivunen et al, 2003). Consistent with this work, a recent study showed in in vivo experiments, using the endogenous human HIF-1a protein, that both prolyl hydroxylation was more sensitive to inhibition to hypoxia (Hx) than asparaginyl hydroxylation (Tian et al, 2011). Thus, the PHD activity should be more sensitive to a moderate decrease in oxygen compared with that of FIH.…”
Section: Introductionsupporting
confidence: 53%
“…It is noteworthy that overexpression of FIH-1 results in a decrease in HIF-1␣ activity even under hypoxic (1% O 2 ) conditions, similar to what was seen previously for PHD2 activity in NP cells (10). Moreover, these results are consistent with previous findings that the in vitro K m for O 2 of FIH-1 is much smaller (90 M) than that of PHD2 (250 M) (32,33) and that substantial levels of hydroxylated Asn 803 can be detected even at 0.1% O 2 (20) in RCC4 and MCF7 cells, suggesting preservation of FIH-1 enzymatic function under hypoxia. Furthermore, a very recent report that FIH-1 can still suppress HIF-dependent GLUT1 and VEGF-A expression in hypoxic glioblastoma in vitro and also in vivo in a xenograft model supports this idea (34).…”
Section: Discussionsupporting
confidence: 81%
“…This post-translational modification of a specific Asn residue prevents binding to p300/CBP, thereby suppressing HIF-1/2 transcriptional activity (18,19). Noteworthy, because the K m of FIH-1 for oxygen is significantly lower than that of PHD1-3, even under conditions of moderate hypoxia, such as those present in the NP, FIH-1 activity is preserved (20). Thus, controlling expression/activity of FIH-1 is one of the important ways cells control HIF transcriptional activity.…”
mentioning
confidence: 99%
“…In the presence of oxygen (normoxia), HIF-1a is hydroxylated by prolyl hydroxylase at prolines 402 and 564 and then recognized by the von Hippel-Lindau (VHL) protein, ubiquitinated by E3 ubiquitin ligase, and degraded rapidly via the proteasome pathway (4). HIF-1a is also hydroxylated by asparaginyl hydroxylase at asparagine 803 and blocks its interaction with the transcriptional coactivators CBP and p300 (5). Both prolyl and asparaginyl hydroxylation are inhibited under the hypoxic condition, which allows HIF1a to accumulate and subsequently leads to the transactivation of hundreds of downstream target genes involved in cell metabolism, survival, angiogenesis, and metastasis (6).…”
Section: Introductionmentioning
confidence: 99%